2022
DOI: 10.1002/pro6.1149
|View full text |Cite
|
Sign up to set email alerts
|

A review of proton therapy – Current status and future directions

Abstract: The original rationale for proton therapy was its highly conformal depth‐dose distributions compared to photons, which allow greater sparing of normal tissues and escalation of tumor doses, thus potentially improving outcomes. Additionally, recent research has revealed previously unrecognized advantages of proton therapy. For instance, the higher relative biological effectiveness (RBE) near the end of the proton range can be exploited to increase the difference in biologically effective dose in tumors versus n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 117 publications
0
56
0
1
Order By: Relevance
“…Several studies have also revealed previously unrecognized biological advantages of proton therapy (PT) specifically [ 177 ]. Moreover, the lower integral dose of PT and its dose sparing properties, have been found to reduce the exposure of circulating lymphocytes and the immune organs at risk compared to photon-based RT [ 178 ]. Preliminary findings of a study in NSCLC with underlying idiopathic pulmonary fibrosis showed a trend of non-statistically significant better OS compared to X-rays for patients treated with PT [ 179 ].…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also revealed previously unrecognized biological advantages of proton therapy (PT) specifically [ 177 ]. Moreover, the lower integral dose of PT and its dose sparing properties, have been found to reduce the exposure of circulating lymphocytes and the immune organs at risk compared to photon-based RT [ 178 ]. Preliminary findings of a study in NSCLC with underlying idiopathic pulmonary fibrosis showed a trend of non-statistically significant better OS compared to X-rays for patients treated with PT [ 179 ].…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The higher RBE at the distal edge of the beam could potentially be problematic if this region is deposited in an organ at risk such as the heart. When one applies generous margins to circumvent the problem of tumour motion and tissue heterogeneity, this might counteract the dosimetric advantage and cause more normal tissue injury [ 178 ]. This adds an additional layer of complexity in the incorporation of proton therapy with RE seeing as microvascular heterogeneity is another important variable to consider due to its abundance in lung tissue [ 183 ], and its direct influence on the efficacy of anti-angiogenic therapy.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The finite range and sharp distal fall-off characteristics of protons allow radiation dose to be delivered to a specific depth using the spread-out Bragg peak. The distant normal tissue receives a negligible radiation dose [16,30]. More conformal dose distributions can be achieved due to the ability of IMPT to control the beamlet energies and intensities.…”
Section: Discussionmentioning
confidence: 99%
“…Since protons have a larger penumbra, normal tissues near the target may receive a higher radiation dose [16]. Xu et al reported that compared to IMRT, proton therapy performed poorly in decreasing the irradiated volume of PBM in the high-dose region (33.9-42.9 Gy), and the PBM V 40 increased by 14.6%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation